Triacylglycerols: Fuelling the Hibernating Mycobacterium tuberculosis - Maurya, Rahul Kumar; Bharti, Suman; Krishnan, Manju Y. (Frontiers in Cellular and Infection Microbiology, 2019)
Mycobacterium tuberculosis (Mtb) has the remarkable ability to persist with a modified metabolic status and phenotypic drug tolerance for long periods in the host without producing symptoms of active tuberculosis. These persisters may reactivate to cause active disease when the immune system becomes disrupted or compromised. Thus the infected hosts with the persisters serve as natural reservoir of the deadly pathogen. Understanding the host and bacterial factors contributing to Mtb persistence is important to devise strategies to tackle the Mtb persisters. Host lipids act as the major source of carbon and energy for Mtb. Fatty acids derived from the host cells are converted to triacylglycerols (triglycerides or TAG) and stored in the bacterial cytoplasm. TAG serves as a dependable, long-term energy source of lesser molecular mass than other storage molecules like glycogen. TAG are found in substantial amounts in the mycobacterial cell wall. This review discusses the production, accumulation and possible roles of TAG in mycobacteria, pointing out the aspects that remain to be explored. Finally, the essentiality of TAG synthesis for Mtb is discussed with implications for identification of intervention strategies.